Novel 1,3,4-oxadiazole-nicotinamide hybrids as non-classical AHL mimics quorum sensing inhibitors of Pseudomonas aeruginosa: design, synthesis and biological evaluation - Mohamed M. S. Hamoud; Amany M. Ghanim; Abdalla E. A. Hassan; Hanan A. Abdel-Fattah; Hisham A. Abbas; Noura M. Seleem; Hend Kothayer; Nermine A. Osman (BMC Chemistry)
Abstract Pseudomonas aeruginosa employs N-acylated L-homoserine lactones (AHLs) as autoinducers (AIs) for quorum sensing, which in the end is responsible for biofilm and virulence factor production along with the development of antibiotic resistance in bacteria. Here, we designed and synthesized a library of S-alkyl-1,3,4-oxadiazoles bearing nicotinamide moiety targeting AHLs receptors (LasR and RhlR) and evaluated their efficacy as new inhibitors of quorum sensing. The minimum inhibitory concentrations of the synthesized compounds against P. aeruginosa PAO1 were determined, and they ranged from 2.5 to 5 mg/ml. All the compounds were subjected to further investigation against protease and pyocyanin. The oxadiazole derivative 3a was the most potent compound that reduced both protease activity and pyocyanin production by 38.46% and 70.27% respectively. Moreover, compound 3a showed a significant reduction of the biofilm formation by 81.72%. A docking study was performed to explore the potential binding interactions with quorum-sensing receptors (LasR and RhlR), which are responsible for the expression of virulence genes. Molecular docking results indicated that compound 3a showed a comparable binding affinity to the co-crystalized ligands of two P. aeruginosa QS targets (lasR and RhlR) with higher affinity towards LasR than RhIR active sites. Our findings highlight the promising potential of 1,3,4-oxadiazole-nicotinamide hybrid 3a as an anti-virulence agent to combat P. aeruginosa. Graphical Abstract